The Role of Muslim Generation Community at Zakat Collection on Realizing Sustainable Development Goals (SDGs) in the Era of Digital Society 5.0 - Rizal Rizal; Ruslan Abdul Ghofur; Pertiwi Utami (Institut Agama Islam Negeri Batusangkar, 2023)
The large potential of zakat funds can support the government’s efforts in alleviating poverty. However, its management has not been seen optimally even though BAZNAS has been designated as the official agency and the only non-structural government agency that manages zakat. This study aims to investigate the important role of the human generation who are members of the Muslim community in collecting zakat at the BAZNAS in the era of digital society 5.0 to realize the SDGs. This study uses a literature study method with library data collection techniques, reading and taking notes, and managing research materials by tracing written sources that have been previously written. This study uses content analysis techniques to obtain written information that focuses on four dimensions, namely human generation, Muslim community, zakat collection, and sustainable development goals. The findings reveal that two generations of humans are members of the Muslim community that have the potential to increase zakat collection. Deeper, Maqāṣid shari’āh as the essence of Islamic law through the values of justice, freedom, and human rights of the Muslim community will support the goal of collecting zakat. The novelty of this research found that building the strength and glory of BAZNAS in the era of digital society 5.0 requires strong social ties from the entire Muslim generation community, especially the younger generation community. The main contribution of this research highlights the ‘zakat movement’ led by BAZNAS to pay more attention to the role of the millennial Muslim generation community and iGeneration in supporting zakat empowerment programs to realize Sustainable Development Goals.